2020
DOI: 10.1038/s41598-020-73729-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Melissa officinalis extract containing rosmarinic acid in the prevention of Alzheimer’s disease progression

Abstract: We conducted a randomized placebo-controlled double-blind 24-week trial using Melissa officinalis (M. officinalis) extract richly containing rosmarinic acid (RA) on patients with mild dementia due to Alzheimer’s disease (AD) with the aim to examine the safety and tolerability (primary endpoint) of RA (500 mg daily) and its clinical effects and disease-related biomarker changes (secondary endpoints). Patients (n = 23) diagnosed with mild dementia due to probable AD were randomized to either the placebo or M. of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…Table S1 provides a summary of the baseline characteristics of the 34 eligible RCTs 20‐54 (35 references were included because cognitive and biological outcomes and safety outcomes of one phase II RCT were reported in 2 references 30,40 respectively). Four (11.8%) were phase I studies, 20,31,34,39 seventeen (50%) were phase II studies, 21‐23,25,26,28,30,32,33,35,36,38,41,49‐51,53 five (14.7%) were phase III studies, 24,27,29,43,54 and one (2.9%) was a phase II/III study 37 . Typical patients were between 67 and 81 years of age, and the majority were women.…”
Section: Resultsmentioning
confidence: 99%
“…Table S1 provides a summary of the baseline characteristics of the 34 eligible RCTs 20‐54 (35 references were included because cognitive and biological outcomes and safety outcomes of one phase II RCT were reported in 2 references 30,40 respectively). Four (11.8%) were phase I studies, 20,31,34,39 seventeen (50%) were phase II studies, 21‐23,25,26,28,30,32,33,35,36,38,41,49‐51,53 five (14.7%) were phase III studies, 24,27,29,43,54 and one (2.9%) was a phase II/III study 37 . Typical patients were between 67 and 81 years of age, and the majority were women.…”
Section: Resultsmentioning
confidence: 99%
“…A clinical study in the literature has shown that chronic administration of a lemon balm extract in a daily dose of 500 mg improves the cognitive abilities of patients suffering from Alzheimer’s disease with mild associated dementia, with a reduction in the cellular senescence process. Intriguingly, the used extract had a high RA content [ 44 ]. Once we had assessed the effect of the RA on neuroinflammation and microglial senescence using the in vitro model, we moved on to test it in an in vivo model of peripheral neuropathy, the SNI.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that RA exerted protective effects on Aβ evoked oxidative stress via Akt/GSK-3β/Fyn pathway through upregulation of nuclear factor E2-related factor (Nrf2) activity (Rong et al 2018 ). Previous studies have reported the clinical effectiveness of RA-rich Melissa officinalis in preventing AD progression (Noguchi-Shinohara et al 2020 ) . The safety of RA (from Melissa officinalis ) consumption was evaluated in a randomized-placebo controlled double-blind trial conducted for 24 weeks on subjects with mild dementia associated with AD.…”
Section: Clinical Implications Of Ramentioning
confidence: 99%